COVID-19-Associated Biventricular Takotsubo Syndrome Complicated with Cardiogenic Shock (Clinical Case) - E. M. Zeltyn-Аbramov; N. I. Belavina; N. N. Klochkova; R. T. Iskhakov; O. Yu. Evsyukov; L. Yu. Аrtyukhina; A. M. Svanadze; M. A. Lysenko (Вестник анестезиологии и реаниматологии, 2022)
Acute myocardial dysfunction (AMD) remains prominent among extrapulmonary manifestations of COVID-19. Takotsubo syndrome (TS) is one of the causes of AMD development. TS incidence in patients with COVID-19 is currently unknown. The report presents a clinical case of an elderly female patient on maintenance hemodialysis with severe COVID-19. During the session of therapeutic plasma exchange (TPE), the patient had an episode of ventricular fibrillation followed by cardiogenic shock development and ECG changes, similar to myocardial infarction. Echocardiographic (Echo) data showed a distinctive pattern of biventricular TS with a significant systolic function decrease in both ventricles. Emergency CT angiography ruled out obstructive lesions of coronary arteries. Full recovery of both ventricles systolic function, regression of ECG changes, and complete resolution of cardiogenic shock were observed within the next week. The subsequent course of the disease was complicated by sepsis and multiple organ failure which determined the lethal outcome.The autopsy findings excluded coronarogenic and viral myocardial damage. The presented case demonstrates a life-threatening TS pattern in patients with severe COVID-19. TPE procedure should be treated as a possible trigger of TS.